(untitled) (Panacea Journal of Medical Sciences, 2022)
Background: In a densely populated country like India, the COVID-19 pandemic poses a major concern in front of the already overworked healthcare workers. Paramedical staff deals with patients of COVID-19 throughout their stay in the hospital and hence these workers are susceptible to the psychological changes followed by this stressful exposure. If these symptoms are dealt with in a professional manner and if they receive proper care then their work efficiency will improve immensely. Materials and Methods: A cross-sectional study was carried out in 65 consecutively selected paramedical staff including 45 nurses and 20 attendants. They were interviewed telephonically after taking their informed consent. Data was collected using semi-structured proforma, Hamilton Anxiety Rating Scale (HAM-A) and Hamilton Depression Rating Scale (HAM-D). Statistical analysis was done using mean, chi square test. Results: Statistically significant difference was found between married and unmarried participants in total Ham-A score (mean score 7.75 in married and 3.85 in unmarried, P=0.0008); insomnia early in the night (28.57% in married and 61.36% in unmarried, P=0.033); anxiety psychic (76.19% in unmarried and 84.09% in married; P=0.004); anxiety somatic (61.9% in unmarried and 84.09% in married, P= 0.012); Somatic symptoms gastrointestinal (19.05% in unmarried and 61.36% in married, P=0.006); general somatic symptoms (28.57% in unmarried and 68.18% in married, P=0.006); HAM-D total score (mean score 2.90 in unmarried and 6.06 in married, P=0.0003). Conclusion: 1. Paramedical staff working in COVID-19 wards are susceptible for psychological symptoms; 2. Anxious mood was the most common symptom reported.